Pengaruh Fasilitas Dan Lokasi Usaha Terhadap Keputusan Berkunjung Di BullsGym EcoClub Cabang Citra Raya - Yosa Nugroho; Fadillah Fadillah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of facilities and business location on the decision to visit BullsGym EcoClub Citra Raya. This study uses a quantitative method. The population in this study is all members of BullsGym EcoClub Citra Raya, with a sample of 116 respondents using accidental sampling technique. Data analysis techniques used multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results show that facilities and business location have a significant effect on visiting decisions with a correlation coefficient value between facilities and visiting decisions of 0.811, indicating a strong relationship, and a coefficient of determination (R Square) value of 0.286. The hypothesis test showed a t-value > t-table (7.172 > 1.980), so H₀₁ was rejected and H₁ was accepted. Meanwhile, the correlation coefficient between business location and visit decisions was 0.683, indicating a strong relationship, and the coefficient of determination (R Square) was 0.542. The hypothesis test shows that the t-value is greater than the t-table value (11.972 > 1.980), so H₀₂ is rejected and H₂ is accepted. Simultaneously, facilities and business location have a significant effect on decision to visit with the multiple linear regression equation Y = 7.004 + 0.204 X1 + 0.200 X2. A correlation coefficient value of 0.811 indicates a very strong relationship, with an R Square value of 0.685 or 68.50%. The F test shows that Fcount > Ftable (122.888 > 3.08), so H₀₃ is rejected and H₃ is accepted. Thus, it can be concluded that facilities and business location have a positive and significant effect on the decision to visit BullsGym EcoClub Citra Raya